A PUBLIC HEALTH GENOMICS PERSPECTIVE FOR OBESITY - Brettfeld, C.; Taneri, B.; Haslberger, A. (Karger, 2013)
[Abstract Not Available]
Keywords: Obesity; genetics; epigenetics; gene-environment interactions (GxE); public health; public health genomcis